Nutritional Status and Body Composition in Patients Suffering From Chronic Respiratory Diseases and Its Correlation With Pulmonary Rehabilitation - Wouters, Emiel F. M. (Frontiers in Rehabilitation Sciences, 2021)
As part of an individualized intervention to improve the physical, emotional and social functioning of patients with chronic respiratory diseases in general and COPD in particular, awareness of the presence and consequences of changes in body composition increased enormously during the last decades and nutritional intervention is considered as an essential component in the comprehensive approach of these patients. This review describe the prevalence as well as clinical impact of body composition changes and provides an update of current intervention strategies. It is argued that body composition, preferentially a three-component evaluation of fat, lean and bone mass, must become part of a thorough assessment of every patient, admitted for pulmonary rehabilitation.